Improving Teachers' Pedagogic Competence in Preparing Lesson Plan Through Workshops for Preparation of Lesson Plan at MGMP Activities in MTSN 4 Padang - Hayati, Nur (The Future of Education Journal, 2023)
This research is motivated by the results of observations and results of the assessment results of lesson plans for Physical Education teachers at MTsN 4 Padang. Where the number of Penjasorkes teachers is 4 people and teachers are still not able to compile lesson plans in accordance with the limitations of writing lesson plans. To overcome this problem, a lesson plan preparation workshop will be held at the MGMP Activities at MTsN 4 Padang. This research is a madrasah action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The subjects of this study were 4 Physical Education teachers at MTsN 4 Padang. Research data was collected using observation sheets. Based on the results of the research and discussion that have been put forward in the previous chapter, it can be concluded that the RPP Preparation Workshop through the MGMP can improve teachers' abilities in making RPP in Physical Education subjects. This is evidenced by an increase in the ability of teachers to prepare lesson plans from cycle I to cycle II. The average teacher's ability to prepare lesson plans in the first cycle was 73.06 in the sufficient category and in the second cycle was 84.23 in the good category.